Regulation of the aryl hydrocarbon receptor in cancer and cancer stem cells of gynecological malignancies: An update on signaling pathways - Lubna Therachiyil (4246156) (2022)
Gynecological malignancies are a female type of cancers that affects the reproductive system. Cancer metastasis or recurrence mediated by cellular invasiveness occurs at advanced stages of cancer progression. Cancer Stem Cells (CSCs) enrichment in tumors leads to chemoresistance, which results in cancer mortality. Exposure to environmental pollutants such as polycyclic aromatic hydrocarbons is associated with an increased the risk of CSC enrichment in gynecological cancers. One of the important pathways that mediates the metabolism and bioactivation of these environmental chemicals is the transcription factor, aryl hydrocarbon receptor (AhR). The present review explores the molecular mechanisms regulating the crosstalk and interaction of the AhR with cancer-related signaling pathways, such as apoptosis, epithelial-mesenchymal transition, immune checkpoints, and G-protein-coupled receptors in several gynecological malignancies such as ovarian, uterine, endometrial, and cervical cancers. The review also discusses the potential of targeting the AhR pathway as a novel chemo-therapy for gynecological cancers. Other Information Published in: Seminars in Cancer Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.semcancer.2022.10.003